Looking through goal theories in language learning: A review on goal setting and achievement goal theory - Xiaofang Cheng (Frontiers in Psychology, 2023)
A growing interest can be seen in the studies on the motivation related to second/foreign learning in recent decades. All in all, research verdicts designate that academic motivation plays a key function in the extent to which students are successful in their research. One of the dimensions of academic motivation is goal orientation, which accounts for why learners carry out achievement activities. This type of goal is indicative of the importance one attaches to success concerning a performance standard. Furthermore, goal setting is deemed as a significant cognitive interface that connects motivation to motivational behavior. Indeed, goal setting is an inseparable part of L2 learning that has caught the attention of many researchers. It functions as a booster of motivation and success in various fields. Goals render the activities purposeful, providing individuals with directions. Moreover, goal drives them to invest more resources and effort, pushing them to persevere in learning. The new versions of motivational theories emphasize social-cognitive components underlying motivated behavior. Therefore, they are more inclusive than traditional ones. Achievement goal theory (AGT) has been developed as a motivation-related theory in recent decades. This theory serves as an effective framework to account for motivation associated with social achievement and learning environments. It also deals with the outcomes concerning cognitive and behavioral aspects. Another theory related to motivation is the Goal setting theory, which functions as a cognitive mediator between motivation and second/foreign learning behavior. It also impacts the students’ application of strategies. Drawing on the recent conceptual developments, this review seeks to make a contribution to the related literature on theories of achievement goals, i.e., AGT and goal setting associated with the L2 context. Such a review has pedagogical implications for EFL stakeholders.